Poverty and Income Effects on Voluntary Association Membership: A Cross-National Comparison - Duncan, Laura J. (My University, 2006)
This study examines the influence of individual income and contextual poverty and income inequality on voluntary association membership in Canada and the influence of individual income and contextual poverty cross-nationally. Applying multilevel modelling techniques to data from the 2003 Canadian General Social Survey, the 2001 Census, the 1981-2004 World Values Survey and country-level data on poverty, economic development and religious attendance this study pursues two lines of questioning. The first investigates how individual income level, area poverty and area income inequality affect voluntary association membership in Canada. The second investigates how individual income and contextual poverty affect voluntary association membership across 55 countries. The findings of this study advance our understanding of individual and contextual economic influences on voluntary association membership in new ways, both in terms of the content of the findings and the methods used to categorise voluntary association membership. The findings support claims about the negative effects of individual economic disadvantage, contextual economic inequality and poverty. In doing so, this study contributes important findings to the discipline of sociology and the wider society.
Keywords: Sociology; Sociology